Developing Social Skills in a School Environment: a proposal involving the Good Behavior Game (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The Good Behavior Game (GBG) is a management technique aimed at reduce/prevent disruptive behaviors in an educational context. This research sought to verify if, the use of strategies based on a variation of the GBG, would facilitate the development of prosocial behaviors positively reinforced in the fifth graders. The experimental lineation was divided into two phases: a week of baseline to verify the frequency of emission of the behaviors to be evaluated; and four weeks of observations to the score recording of the groups according to the desirable behaviors. At the end of each week of observation, prizes were given to the winner group. The results showed that the use of positive reinforcement is important for the development of competences and skills social in the school context. It is concluded that it is possible to utilize a positive variation of the GBG producing a conducive environment to the cognitive and rational process of the students.
Keywords: Good Behavior Game; Social abilities; Socioemocional abilities; Scholar psychology; Positive reinforcement